(3GdbSWGS aj GdYQhVs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdCLd GdRGgO LGQ Gddg CUfGa GdYdhe GdCOHjI JQJbi Edi EKfi YTQ UfakG GdChd Yde GddZI GdKGfi Yde GdCHfjI GdKGdK Yde GdETJbGb s
(3BNQgG (B:s
(3ChbaJ Ydi Wdd WQHkG aTLGc hCMRfc GdWdd eNHhf cdg bGd GdeDda hUdJ Edi eG hLgJ hcOi Edjg hYdeJ HgeJi fMhg ef EJeGe GdcJGH hGdMeO ddg Ydi Pdc Ke GdUdGI hGdSdGe Ydi SjOfG eMeO hGdg hUMHg CLeYjf hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1326s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais